2013
DOI: 10.1262/jrd.2013-015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ethylene Glycol and Propylene Glycol for the Vitrification of Immature Porcine Oocytes

Abstract: Our aim was to optimize a cryoprotectant treatment for vitrification of immature porcine cumulus-oocyte complexes (COCs). Immature COCs were vitrified either in 35% ethylene glycol (EG), 35% propylene glycol (PG) or a combination of 17.5% EG and 17.5% PG. After warming, the COCs were in vitro matured (IVM), and surviving oocytes were in vitro fertilized (IVF) and cultured. The mean survival rate of vitrified oocytes in 35% PG (73.9%) was higher (P<0.05) than that in 35% EG (27.8%). Oocyte maturation rates did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
34
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 22 publications
10
34
1
1
Order By: Relevance
“…Our results are similar to those previously reported for EG-based media [1,22]. However, Somfai et al [41,46] recently reported viability of approximately 28% using EG as the only permeant CPA and 42.6% viability with a combination of EG þ PG [46]. Although the differences in viability between the studies could be due to technical aspects of the vitrification procedure or the quality of the oocytes used, the dissimilarities in the final CPA concentration, which was 32% in our study and 35% in Somfai et al [46], could play a key role.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results are similar to those previously reported for EG-based media [1,22]. However, Somfai et al [41,46] recently reported viability of approximately 28% using EG as the only permeant CPA and 42.6% viability with a combination of EG þ PG [46]. Although the differences in viability between the studies could be due to technical aspects of the vitrification procedure or the quality of the oocytes used, the dissimilarities in the final CPA concentration, which was 32% in our study and 35% in Somfai et al [46], could play a key role.…”
Section: Discussionsupporting
confidence: 93%
“…Although the reasons for these differences are unclear, the results suggest that the higher permeability of PG better protects oocytes compared with DMSO in terms of fertilization efficiency. As in previous studies [10,13,46], our results indicate that regardless of CPA combination, vitrified oocytes exhibit a reduced ability to develop to the blastocyst stage after IVF compared with controls.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations